An Adaptive Mobile Robot with Gaussian type on Fuzzy Logic Type 2 - Siti Nur Aliza, Azmi (2022)
This is an adaptive Mobile Robot Navigation project based on Fuzzy Logic Type 2. The goal of this study is to investigate the performance of a mobile robot in an environment (navigation). As a result, this project will be emphasized on the outcomes of simulation for the mobile robot in navigation. The background for the simulation will be based on the obstacle avoidance. In brief, when the fuzzy controller detects any potential obstacle nearer or on the way for the robot going to the goal point, the robot will be able to avoid it. In navigation, the surrounding environment for the robot and the position of the obstacle should be understood ahead of time. The robot is required to navigate to its destination by avoiding the obstacle. In such, the robot navigation in simulations can be estimated using prior information of the coordinates from the beginning point, the goal point, and the obstacle position. Thus, in this research, the cost function method was implemented to evaluate and estimate the robot's surroundings in a simulated environment. Consequently, the objective of the project is to design a mobile robot in navigation using the fuzzy logic system and to develop the lower state estimation error for both estimated and measured simulation value. By using the cost function and fuzzy logic, the mobile robot navigation was proved as the result shows that the robot was able to avoid the obstacle on its way toward the goal point. Furthermore, the graph shows only a slight difference occurred between the measured and estimated values, indicating that the project was implemented as required.